Sustainable Practices and Tourism Reactivation in Travel Agencies in Peru - Chura, Delia Condori; Suaquita, Jhon Richard Huanca; Torreblanca, Felix Abelardo Arizaca; Auquitias-Condori, Gladys; Cayo-Velásquez, Noemi Emperatriz; Apaza-Tarqui, Alejandro (Journal of Posthumanism, 2025)
The study reveals a direct and significant relationship between economic impact and tourism reactivation in wholesale travel agencies in Peru. It highlights the importance of economic growth strategies for the revival of tourism. In addition, a moderate relationship is identified between social impact and tourism reactivation, highlighting the importance of promoting a positive social impact. A significant correlation is observed between sustainable development practices and tourism recovery, highlighting the importance of an effective organizational culture. This original correlational design study evaluates the relationship between sustainable development and tourism recovery in travel agencies in Peru. It implies that sustainable practices and a focus on economic and social impact are crucial for agency success and sustainable tourism growth. Further research on specific sustainable development strategies and cultural factors is suggested for future research.